Harmoni di Tengah Puing: Potret Solidaritas Lintas Agama Mahasiswa Hukum UINSU Pasca Bencana Alam di Sumatera Utara dan Aceh (Jurnal Riset Rumpun Agama dan Filsafat, 2024)
This study aims to analyze the interfaith solidarity of UINSU Law students after natural disasters in North Sumatra and Aceh and to identify the forms of social activities and humanitarian values developed through these humanitarian actions. The research method used is a qualitative method with a field research approach through observation, interviews, and documentation. The research data sources were obtained from students, social volunteers, and disaster-affected communities involved in humanitarian activities. The results of the study indicate that UINSU Law students have an important role in helping communities through fundraising activities, humanitarian volunteers, psychosocial assistance, and interfaith cooperation. The interfaith solidarity carried out by the students was able to strengthen social relationships, increase tolerance, and create social harmony in post-disaster communities. In addition, the values of religious moderation, social concern, and unity became the main foundations of the students’ humanitarian activities. The presence of students among disaster victims gave a positive impact on the social recovery process and strengthened the sense of brotherhood and humanity within Indonesia’s multicultural society.